IMPLEMENTASI PIOMI PADA BAYI DENGAN BERAT BADAN LAHIR SANGAT RENDAH - Salsabila Izzaturrohmah; Zubaidah Zubaidah (Nurse and Health: Jurnal Keperawatan, 2023)
Background: Very low birth weight is a condition of babies with a birth weight of less than 1500 grams. Premature or preterm babies are prone to nutrition deficiencies due to inadequate suction reflexes and inability of the digestive tract to absorb nutrients. Preterm Infant Oral Motor Intervention as known as PIOMI is an intervention used to stimulate the sucking reflex. The PIOMI intervention was carried out by massaging and stimulating the oral cavity, cheeks, and tongue before feeding once a day. Objectives: This study aims to analyze the effect of administration of the PIOMI intervention on weight gain, increased intake and increasing LATCH on, Audible of swallowing, Type of nipple, Comfort level, Hold positioning as known as LATCH score. Methods: This case study type experimental research design with nursing care approach. The population of this study consisted of very low birth preterm (<1200 grams) newborns. The study sample included 1 single case of very low birth weight preterm newborns, resulting from the strength analysis, who were treated in high risk neonatal unit university hospital. Data were collected using the Preterm Infant Chart Form and LATCH Breastfeeding Scale. PIOMI intervention was conducted for 7 consecutive days. Nutritional status evaluated each day and the sucking successes were evaluated at day 1 and day 7. Results: The results indicated that after the intervention for 7 consecutive days the weight and diet increased. There was also an increase in the LATCH score before treatment until prior to discharge from the hospital (7-9). Conclusion: Administration of PIOMI is expected to prevent delays in oral feeding, increasing LATCH score and overcome nutritional deficiencies in low birth weight infants.